Perlindungan Hukum Terhadap Tenaga Kerja Sebagai Kreditur Istimewa - Arapenta, Deary Christian; Karsona, Agus Mulya; Sari, Deviana Yunita (JURNAL USM LAW REVIEW, 2024)
This research analyzes the impact of corporate bankruptcy and the legal protection that must be provided to workers, particularly regarding the normative rights that workers are entitled to receive. In such circumstances, workers' normative rights, such as wages, severance pay, and benefits, are often not fulfilled. Workers are in a weak position as creditors in bankruptcy proceedings, as the regulations prioritize secured creditors. This research employs the normative juridical method. The novelty of this research lies in the comprehensive analysis of legal certainty and justice for workers as preferred creditors in bankruptcy cases, as well as the proposal for legal reforms to harmonize conflicting regulations to strengthen the protection of workers' normative rights. The conclusion drawn from the discussion is that workers, as preferred creditors, must be prioritized in the payment of bankruptcy debts. There is a need for stricter supervision, stronger legal protection for workers in bankruptcy proceedings, and the necessity for reforms in bankruptcy law, especially in the mechanism for the settlement and distribution of bankruptcy assets to each creditor. Penelitian ini bertujuan untuk menganalisis dampak kepailitan perusahaan dan bagaimana perlindungan hukum yang harus diberikan kepada tenaga kerja, terutama hak-hak normatif yang harus diterima pekerja. Dalam kondisi ini, hak-hak normatif pekerja, seperti gaji, pesangon, dan tunjangan, sering kali tidak dipenuhi. Pekerja berada pada posisi yang lemah sebagai kreditur dalam proses kepailitan, karena aturan lebih mengutamakan kreditur yang memiliki jaminan. Yuridis normatif adalah metode penelitian yang digunakan dalam penelitian ini. Kebaruan penelitian ini terletak pada analisis komprehensif mengenai kepastian hukum dan keadilan bagi pekerja sebagai kreditur preferen dalam kasus kepailitan, serta usulan reformasi hukum untuk menyelaraskan peraturan yang bertentangan guna memperkuat perlindungan hak-hak normatif pekerja. Kesimpulan yang dapat diambil dari hasil pembahasan bahwa pekerja sebagai kreditur preferen harus didahulukan dalam pembayaran utang pailit, diperlukan pengawasan yang lebih ketat, perlindungan hukum yang lebih kuat bagi tenaga kerja dalam proses kepailitan, dan diharuskan adanya pembaharuan undang-undang kepailitan khususnya dalam mekanisme pemberesan dan pembagian boedel pailit kepada masing-masing kreditur.